Classification of surface temperature for the flexible pavement design - Kleizienė, Rita; Vaitkus, Audrius; Židanavičiūtė, Jurgita; Marcinkevičius, Evaldas (International Conference “Environmental Engineering”, 2017)
Surface temperature significantly affects the asphalt layers modulus and entire pavement structure response to vehicles traffic loading. Because of the rheological properties of bitumen binders, the asphalt performs similarly to temperature-susceptible visco-elastic materials. The historical temperature data of local regions is necessary to design sustainable pavement structures. Likewise, the layers’ material mechanical properties determined at specific temperatures is essential for proper design too. This paper presents an analysis of pavement surface temperature classification results. Data analysis covers temperature data from the Road Weather Information Stations from the past ten years. An analysis of various temperature profile forecast methods is presented, followed by a review of recent research on the impact of temperature and cause of failure. Particular emphasis is laid on sorting the qualitative temperature data. The complete linkage clustering method had been used for establishing the most similar pairs for classification. Accordingly, the territory of Lithuania was divided into three main regions with different pavement temperature distributions for each temperature interval. Temperature classification along these lines enables pavement responses to be estimated over the pavement design life.